Relación entre las dimensiones de la experiencia de marca y la lealtad de los adultos jóvenes entre los 20 a 29 años en 6 bares de las zonas 6 y 7 de Lima Metropolitana - Sousa Iparraguirre, Brenda Melissa (2023)
The purpose of this research work is to determine the existing relationship between the dimensions of the brand experience and the loyalty of young adults between 20 and 29 years in 6 bars in zones 6 and 7 of Metropolitan Lima, to study the way in which that one has repercussions on the other and to what extent. The study has a quantitative approach and has as a sample young people within the age range mentioned above who have attended at least one of the 6 bars under study. When analyzing the results obtained in the surveys carried out using statistical models, we were able to conclude that both variables studied, experience and loyalty, have a direct and strong relationship. Allowing to affirm that as companies in the bar industry have a focus focused on offering a unique experience that also involves the user and generates satisfaction, they will generate greater loyalty and long-term relationship with their consumers.